Characteristics of TP53 germline variants and their correlations with Li-Fraumeni syndrome or Li-Fraumeni-like syndrome in Chinese tumor patients. (July 2022) - Tian, Panwen; Zhang, Xiaoyan; Yang, Sheng; Fang, Yu; Yuan, Hongling; Li, Wei; Zhu, Honglin; Zhao, Fangping; Ding, Jinlei; Zhu, Yunshu; Wang, Sizhen; Sun, Guochen; et al.
Abstract: Li-Fraumeni syndrome (LFS), a rare autosomal-dominant inheritance condition, is associated with a family cancer history as well as pathogenic/likely-pathogenic TP53 germline variants (P/LP TP5 3 GV). The current clinical methods for detecting LFS are limited. Here, we retrospectively investigate P/LP TP5 3 GV among Chinese cancer patients by next-generation sequencing and evaluate its relationship with a family cancer history. A total of 270 out of 19, 226 cancer patients have TP5 3 GV, including 53 patients with P/LP TP5 3 GV. Patients with P/LP TP5 3 GV are mainly found in male with glioma, lung cancer or sarcoma. The median age of diagnosis for P/LP TP5 3 GV patients is significantly lower than that of non-P/LP TP5 3 GV patients (31-years vs. 53-years; P  < 0.01). One LFS patient and 3 Li-Fraumeni-like syndrome (LFL) patients are among the 26 followed-up P/LP TP5 3 GV patients. Among 25 types of P/LP TP5 3 GV, the highest variant frequencies occurred at codon 175 and 248. p.M237I, p.R158H, p.C238Y and p.C275R, are firstly identified among the Chinese LFS/LFL patients. This study reports the (P/LP) TP5 3 GV characteristics of Chinese pan-cancer patients. These findings suggest analyzing the P/LP TP5 3 GV in cancer patients is an effective strategy for identifying cancer predisposition syndrome.